Higher analogues of discrete topological complexity - Alabay, Hilal; Borat, Ayse; Cihangirli, Esra; Erdal, Esma Dirican (Springer-Verlag Italia Srl, 2024)
In this paper, we introduce the nth discrete topological complexity and study its properties such as its relation with simplicial Lusternik-Schnirelmann category and how the higher dimensions of discrete topological complexity relate with each other. Moreover, we find a lower bound of n-th discrete topological complexity which is given by the nth usual topological complexity of the geometric realisation of that complex. Furthermore, we give an example for the strict case of that lower bound.
Keywords: Discrete topological complexity; Simplicial Lusternik Schnirelmann category; Simplicial complex